GDP Growth Enticement of Politicians and Earnings Management in Pakistan - Javed, Asma; Maeenuddin,; Hussain, Altaf; Hafeez, Muhammad; Ahmad, Ashfaq (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates how GDP growth incentives of politicians at the macro level can affect earnings manipulation of firms in Pakistan at the micro level. It is conducted by taking data of 80 non-financial sector firms listed on the Pakistan stock exchange for the period of 2009 to 2018. Multiple linear regression and descriptive statistics were used for data analysis. Results revealed that firms that are in those provinces that have a lower level of GDP than the national level are more engaged in manipulating their earnings. But findings couldn’t prove that state-owned enterprises are more involved in earnings management due to the direct influence of political leaders over these public firms. The study provides implications for policymakers to recognize the purposes of earnings management and how incentives from politicians can influence the actions of managers at the firm level.